Homozygous PIGT Mutation Lead to Multiple Congenital Anomalies-Hypotonia Seizures Syndrome 3 - Yang, Li; Peng, Jing; Yin, Xiao-Meng; Pang, Nan; Chen, Chen; Wu, Teng-Hui; Zou, Xiao-Min; Yin, Fei (Frontiers in Genetics, 2018)
PIGT encodes a subunit of the glycosylphosphatidylinositol transamidase complex, which catalyses the attachment of proteins to GPI-anchors. A homozygous PIGT variant c.550G>A (p. E184K) in a Chinese boy with multiple malformations, hypotonia, seizure and profound development delay was identified by panel sequencing. Pathogenicity of the variant was confirmed by flow cytometry. The expression of CD16 and CD24 of this proband reduced to 16.92% and 22.16% compare with normal control respectively while which of his parents and sister were normal. This mutation raised the mRNA level on the peripheral blood mono nuclear cells of this patient. This study expanded the variant spectrum of MCAHS3, and CD16 could be an effective marker to evaluate the pathogenicity of PIGT mutation.